Principes d'expérimentation - Dagnelie, Pierre (Uliège Library, 2012)
Principles of Experimentation: Designing Experiments and Analyzing Their Results introduces the basic concepts of experimentation as the rational use of experimental designs. This book covers the design of such plans as well as the analysis and interpretation of the results obtained. These concepts are presented in a very general manner and are illustrated with numerous examples. The set also includes numerical tables, a bibliographic index of more than 400 references, an index of English translations and a subject index. Additional information is available on a website. This book is intended for teachers, students and researchers in all disciplines who use the experimental method in universities, colleges and public and private research centers. It complements the books Statistical Theory and Methods: Agronomic Applications (2 vols.), originally published in 1969 and 1970, and Theoretical and Applied Statistics (2 vols.), (1998 and subsequent editions).